Internalizing Multicultural Literacy through Sociology Learning in Creating a Harmonious Society - Aulia, Vina; Maftuh, Bunyamin; Wilodati, Wilodati (Jurnal Pendidikan Sosiologi dan Humaniora, 2024)
The diversity in Indonesian society, which is expected to be a capital of wealth, is quite inversely proportional to the current reality. Weak multicultural understanding accompanied by massive information dissemination, diversity in society sometimes becomes one of the background causes of conflict that is influenced by understanding and ability to respond to existing diversity. Through multicultural literacy in sociology learning, it is expected to strengthen understanding and have implications for a harmonious life. So this study aims to describe how the internalization of multicultural literacy through sociology learning in realizing a harmonious society. This research uses a qualitative approach with a systematic literature review method. This research is conducted by the process of collecting, processing and interpreting data. This research reveals that multicultural literacy can strengthen people's understanding so that it can have implications for a harmonious life. Considering that education is the right medium in internalizing multicultural literacy, then through learning sociology, multicultural literacy can strengthen students' understanding so that they can participate in building a harmonious life.